Pemberdayaan Pola Hidup Sehat Masyarakat Desa Lebanisuko Melalui Senam Ceria dan Infused Water - Nanang Abdillah; Ria Resti Fauziah; Nurotun Nimah; Nur Imamah; Shifa Puteri Amelia; Zumrotus Sholihah; Istianah Istianah; Icha Ayu Nur Lailiyah; Salwania NurAulia; Silvia Dwi Anggraeni; Dimas Maulana Rizky; Muhammad Fathur Rohman Hanip (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This Community Service Program (PKM) was conducted in Lebanisuko Village, Wringinanom Subdistrict, Gresik Regency, with the aim of increasing community awareness and implementation of a healthy lifestyle through two main activities: Senam Ceria (Cheerful Gymnastics) and education on the preparation of infused water. The program adopted a Participatory Action Research (PAR) approach, actively involving the community through stages of socialization, demonstration, and participatory practice. The Senam Ceria activity was held weekly as a means to improve physical fitness, strengthen social relationships among residents, and foster enthusiasm for a healthy lifestyle. Meanwhile, the infused water education activity aimed to enhance community nutritional literacy and introduce healthy, locally sourced natural beverages as alternatives to high-sugar packaged drinks. The results showed a significant increase in community participation in physical activities and an improvement in knowledge and habits related to consuming infused water in daily life. Overall, this program successfully promoted sustainable healthy behavior and strengthened social cohesion and togetherness among the residents of Lebanisuko Village.